BCL10 correlates with bad prognosis and immune infiltration of tumor microenvironment in hepatocellular carcinoma. Issue 3 (20th December 2021) - Chen, Hao; Li, Zhenhan; Wu, Fei; Ji, Wenyan; Lu, Linming; Wu, Zhihao; Huang, Yujin; Wang, Wenxiang; Li, Shu
Abstract: It has been reported that B‐cell CLL‐lymphoma 10 (BCL10) serves as an oncogene in cervical cancer. However, the roles of BCL10 in hepatocellular carcinoma (HCC), especially involved in immune infiltration remain not clear. This study aims to explore the relationship between BCL10 and the prognosis and clinical significance, and immune infiltration in HCC. The expression of BCL10 was analyzed between HCC samples and non‐tumor samples in the multiple datasets. In addition, the prognostic values of BCL10 and its methylation in HCC were also investigated. The clinical significance of BCL10 has also been explored. Furthermore, the correlation between BCL10 and immune infiltration in HCC microenvironment was assessed. Finally, the biological behaviors of BCL10 in HCC were verified by cell function experiments. It was found that the expression levels of BCL10 were increased in HCC patients in multiple datasets. Moreover, the increased BCL10 and its reduced methylation were associated with the poor survival. BCL10 was significantly associated with immune infiltration. When BCL10 was knocked down in HCC cells, their proliferation ability was significantly inhibited, their migration was significantly decreased, their apoptosis was significantly increased, and AKT signaling pathway was inhibited. In conclusion, BCL10 is a potential prognostic and diagnostic biomarker related to immune infiltration in HCC microenvironment.